DEVELOPMENT OF SOLID LIPID NANOCARRIERS FOR ORAL DELIVERY OF CANDESERTAN CILEXETIL - (:unkn) unknown (POLSKIE TOWARZYSTWO FARMACEUTYCZNE, 2016)
Candesertan cilexetil is a Biopharmaccutics Classification System (BCS) Class II drug possessing high permeability but low aqueous solubility: hence its oral bioavailability is limited in terms of the solubility rate. The aim of this research was to develop solid lipid nanoparticle (SLN) drug delivery systems of candesertan cilexetil to enhance its aqueous solubility, thereby improving the oral bioavailability of the drug. SLN formulations were produced using a combined technique of high shear homogenization and ultrasonic:Mon method. Drug/lipid and surfactant/co-surfactant ratios of the candesenan cilexetil loaded SLNs were investigated based on various final characteristics of the nanocarriers: namely, encapsulation efficiency, average particle diameter, size distribution, surface charge, thermal behavior, and in vitro drug release profiles. Lipid based nanocarriers of candesertan cilexetil displayed spherical particles having a nanometer size. High encapsulation efficiencies were obtained due to the high lipid solubility of the drug. DSC analysis demonstrated the transformation of the crystalline structure of candesetran cilexetil to amorphous form into the SLN formulations and there was no interaction between the drug and the excipients. Consequently, the oral delivery of candesertan cilexetil with the design of Compritol (R) 888 ATO based lipid nanocarriers may lead to an increase in bioavailability of the drug and thus, more effective therapy may be obtained.
Keywords: candesertan cilexetil; hypertension; SLN; Compritol (R) 888 ATO; Poloxamer (R) 188; oral drug delivery; CANDESARTAN CILEXETIL; NANOPARTICLES; BIOAVAILABILITY; NANOSUSPENSION; OPTIMIZATION; FORMULATION; ABSORPTION